Menantea's Strategy to Attract Gen-Z: The Influence of Brand Image, EWOM, and Lifestyle on Repurchase Intention - Erika Verdiana; Fahrul Riza; Endi Sarwoko (Green Publisher Indonesia, 2025)
This research aims to analyze the influence of brand image, EWOM, and lifestyle on repurchase intention for Menantea brand among Generation Z in Java Island. The study is motivated by the decline in purchases of Menantea products which has led to the closure of many outlets in a relatively short time. The research uses the Theory of planned behavior, which explains that a person's behavior is influenced by their intention to perform that behavior. This intention is determined by three main factors: Theory of planned behavior, subjective norms, and perceived behavioral control. The methodology employed in this study is quantitative descriptive research using questionnaires as research instruments. The targeted respondents are Gen-Z individuals born between 1997-2012, residing in Java Island, who have previously purchased Menantea products. The sample size consists of 100 respondents. This research is expected to provide valuable contributions to Menantea's marketing and branding teams as well as other companies across various business sectors in formulating more effective strategies to enhance repurchase intention. The results indicate that brand image does not significantly affect Menantea's repurchase intention, while EWOM and lifestyle show significant positive influences on repurchase intention among Generation Z consumers of Menantea in Java Island.